Maternal-foetal complications in pregnancy: a retrospective comparison between type 1 and type 2 diabetes mellitus - Valentina Guarnotta; Mariagrazia Irene Mineo; Emanuela Giacchetto; Maria Pia Imbergamo; Carla Giordano (BMC, 2021)
Abstract Background The aim of the study was a retrospective comparison of the differences in maternal-foetal outcomes between women with type 1 and type 2 diabetes mellitus (T1DM and T2DM). Methods A cohort of 135 patients with pregestational diabetes, 73 with T1DM (mean age 29 ± 5 years) and 62 with T2DM (mean age 33 ± 6 years), in intensive insulin treatment throughout pregnancy were evaluated. Clinical and metabolic parameters and the prevalence of maternal and foetal complications were assessed. Results Women with T1DM showed lower pregestational BMI (p < 0.001), pregestational weight (p < 0.001), weight at delivery (p < 0.001), ∆_total_insulin requirement (IR) at the first, second and third trimesters (all p < 0.001) and higher weight gain during pregnancy (p < 0.001), pregestational HbA1c (p = 0.040), HbA1c in the first (p = 0.004), second (p = 0.020) and third (p = 0.010) trimesters compared to T2DM. Women with T1DM had a higher risk of macrosomia (p = 0.005) than T2DM, while women with T2DM showed higher prevalence of abortion (p = 0.037) than T1DM. At multivariate analysis, pregestational BMI and ∆_total_IR of the first trimester were independently associated with abortion in T2DM, while weight gain during pregnancy was independently associated with macrosomia in T1DM. Conclusion Women with T1DM have a higher risk of macrosomia than T2DM due to weight gain throughout pregnancy. By contrast, women with T2DM have a higher risk of spontaneous abortion than T1DM, due to pregestational BMI and ∆_total_IR in the first trimester.